How to reconstruct the lordosis of cervical spine in patients with Hirayama disease? A finite element analysis of biomechanical changes focusing on adjacent segments after anterior cervical discectomy and fusion - Xiao Lu; Fei Zou; Feizhou Lu; Xiaosheng Ma; Xinlei Xia; Jianyuan Jiang (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Purpose To compare the biomechanical changes of adjacent segments between patients with Hirayama disease and non-pathological people after anterior cervical discectomy and fusion (ACDF) operation, and to explore the optimal degree of local lordosis reconstruction during surgery. Methods A young male volunteer was recruited to establish a three-dimensional finite element model of the lower cervical spine based on the CT data. By adjusting the bony structures and simulating the operation process, the models of non-pathological individuals before and after ACDF, patients with Hirayama disease before and after ACDF, and different local lordosis angles were established. Then, the postoperative range of motion (RoM) and stress of the adjacent segments under flexion, extension, left bending, right bending, left rotation and right rotation were recorded and compared. Results The RoM and stress of all segments of lower cervical spine in patients with Hirayama disease are higher than those in non-pathological individual, and this trend still exists after ACDF surgery. When the local lordosis angle is under physiological conditions, the RoM and stress of the adjacent segments are minimum. Conclusion Compared with non-pathological people, Hirayama disease patients have differences in cervical biomechanics, which may lead to cervical hypermobility and overload. After ACDF, the possibility of adjacent segments degeneration is greater than that of non-pathological people. When the operation maintains the physiological local lordosis angle, it can slow down the degeneration.